2020
DOI: 10.1055/s-0040-1713964
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and Consensus among International Orthopaedic Surgeons during Initial and Mid-lockdown Phases of Coronavirus Disease

Abstract: AbstractWith a lot of uncertainty, unclear, and frequently changing management protocols, COVID-19 has significantly impacted the orthopaedic surgical practice during this pandemic crisis. Surgeons around the world needed closed introspection, contemplation, and prospective consensual recommendations for safe surgical practice and prevention of viral contamination. One hundred orthopaedic surgeons from 50 countries were sent a Google online form with a questionnaire explicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Despite the available studies on the impact of the pandemic on the health care system in the world, there are still few reports of how the pandemic and government regulations have affected orthopedic wards. Additionally, the available publications do not directly refer to the level of stress among orthopedic doctors and the process of specialization training for residents, and further education of doctors [6][7][8][9]. Therefore, our research was aimed at identifying the current challenges that orthopedics in Poland is facing in the present circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the available studies on the impact of the pandemic on the health care system in the world, there are still few reports of how the pandemic and government regulations have affected orthopedic wards. Additionally, the available publications do not directly refer to the level of stress among orthopedic doctors and the process of specialization training for residents, and further education of doctors [6][7][8][9]. Therefore, our research was aimed at identifying the current challenges that orthopedics in Poland is facing in the present circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…No similar studies have been published in the OBGYN field, and little data currently exists as to whether societal guidelines were followed by physicians in other fields [ 21 , 22 ]. Pirracchio et al found that the national volume of elective surgeries in all fields dropped precipitously in March 2020, but that the case volume reductions varied greatly by institution [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many applications are being used nowadays to communicate in business/work settings and for personal use. Zoom, Microsoft Teams, FaceTime, and Skype are among the most popular applications used during the COVID-19 pandemic [12]. Regarding the videoconferencing electronic interface/application used by the applicants, 80.2% of the applicants used Zoom.…”
Section: Discussionmentioning
confidence: 99%